Rancang Bangun Sistem Monitoring Progres Pekerjaan Berbasis Website di PT Semen Padang pada Unit Site Engineering - Frevizola, Viona; Irfan, Dedy (Lembaga Yasin AlSys, 2025)
The Site Engineering Unit of PT. Semen Padang plays a critical role in planning, designing, and supervising construction projects as well as maintaining plant infrastructure, encompassing four engineering disciplines. However, the current manual monitoring system—based on Microsoft Excel—has led to several issues, including fragmented data due to weekly reports, a high potential for human error in data recording and processing, and difficulties in updating work progress in real time. This study aims to develop a web-based work progress monitoring system to address these challenges. The system was designed using the Laravel framework for backend development and Vue.js for the frontend, with BlackBox Testing applied to ensure all functions meet user requirements. The results show that the system is accessible across various devices, supports efficient data updates, and enhances coordination among technical disciplines within the project. The study concludes that the developed web-based monitoring system is effective in improving the operational efficiency of the Site Engineering Unit and supports the company's standards in safety, quality, and efficiency for construction and infrastructure maintenance projects.